Ecofeminism Reflected in Chrish Wedge’s Epic (2013) - Agus Ferani Istiharoh (Language and Literature Faculty, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2019)
How nature be treated by a human (female and male) results in the different roles between the genders. Woman, who is associated with nature did such oppression and results in the power hierarchy among genders. This paper discusses one main problem related to the woman in relation to cultural attitudes to nature which is Ecofeminism Reflected in Chris Wedge’s Epic (2013). This research applied the ecofeminism theory. The data were in the form of the movie’s subtitle and the supporting data were taken from books, journals, and other sources related to the topic of discussion. The analysis is presented in the form of a description supported with main data. As a result, the finding states that ecofeminism is represented through the basic existence of nature, different roles between genders, woman’s reactions toward man’s oppression and power hierarchy.